On the Catalytic Activity of [RuH2(PPh3)3(CO)] (PPh3=triphenylphosphine) in Ruthenium‐Catalysed Generation of Hydrogen from Alcohols: a Combined Experimental and DFT study. Issue 11 (9th April 2020) - Lorusso, Patrizia; Ahmad, Shahbaz; Brill (née Schmid), Karin; Cole‐Hamilton, David J.; Sieffert, Nicolas; Bühl, Michael
Abstract: Using density functional theory calculations (at the B97‐D2//BP86 level) and measurements of kinetic isotope effects, we explored the mechanism of [RuH2 (PPh3 )3 (CO)] (22 ) in catalytic acceptor‐less dehydrogenation of methanol to formaldehyde. 22 is found to exhibit a similar activity as the previously studied [RuH2 (H2 )(PPh3 )3 ] (1 b ) complex. On the computed pathway, η 2 →η 1 slippage of Ru‐bound formaldehyde prior to decoordination is indicated to be rate‐limiting, consistent with the low k H / k D KIE of 1.3 measured for this reaction. We also explored computationally the possibility of achieving complete dehydrogenation of methanol (into CO2 and H2 ), through subsequent decarbonylation of formaldehyde and water‐gas shift reaction of the resulting carbonyl complex. Complete pathways of this kind are traced for 22 and for [RuH2 (PPh3 )2 (CO)2 ]. An alternative mechanism, involving a gem‐diol intermediate (obtained upon attack of OH − to coordinated formaldehyde), has also been investigated. All these pathways turned out to be unfavourable kinetically, in keeping with the lack of CO2 evolution experimentally observed in this system. Our calculations show that the reactions are hampered by the low electrophilicities of the CO and HCHO ligands, making OH − uptake unfavourable. Consequently, the subsequent intermediates are too high‐lying on the reaction profiles, thus leading to high kinetic barriers and preventing full dehydrogenation of methanol to occur by this kind of mechanism. Abstract : Reaction mechanisms : Using DFT calculations and measurements of kinetic isotope effects, the mechanism of [RuH2 (PPh3 )3 (CO)] in catalytic acceptor‐less dehydrogenation of methanol to formaldehyde was explored.